Biotherapeutic Approaches in Atopic Dermatitis. Issue 10 (6th April 2020) - Tham, Elizabeth Huiwen; Koh, Elvin; Common, John E. A.; Hwang, In Young
Abstract: The skin microbiome plays a central role in inflammatory skin disorders such as atopic dermatitis (AD). In AD patients, an imbalance between pathogenic Staphylococcus aureus ( S. aureus ) and resident skin symbionts creates a state of dysbiosis which induces immune dysregulation and impairs skin barrier function. There are now exciting new prospects for microbiome‐based interventions for AD prevention. In the hopes of achieving sustained control and management of disease in AD patients, current emerging biotherapeutic strategies aim to harness the skin microbiome associated with health by restoring a more diverse symbiotic skin microbiome, while selectively removing pathogenic S. aureus . Examples of such strategies are demonstrated in skin microbiome transplants, phage‐derived anti‐ S. aureus endolysins, monoclonal antibodies, and quorum sensing (QS) inhibitors. However, further understanding of the skin microbiome and its role in AD pathogenesis is still needed to understand how these biotherapeutics alter the dynamics of the microbiome community; to optimize patient selection, drug delivery, and treatment duration; overcome rapid recolonization upon treatment cessation; and improve efficacy to allow these therapeutic options to eventually reach routine clinical practice. Abstract : Novel approaches to modify the host skin bacteria (microbiome) provide exciting avenues for prevention and treatment of inflammatory skin diseases like atopic dermatitis. This review summarizes the emerging bio‐engineering strategies which aim to harness the skin microbiome associated with health to restore a healthy skin bacterial communities, while selectively removing harmful skin bacteria.